GEOGEBRA APPLETS DESIGN AND DEVELOPMENT FOR JUNIOR HIGH SCHOOL STUDENTS TO LEARN QUADRILATERAL MATHEMATICS CONCEPTS - Nisiyatussani Nisiyatussani; Vidya Ayuningtyas; Maman Fathurrohman; Nurul Anriani (Journal on Mathematics Education, 2018)
This design and development research was motivated by the rapid expansion and use of GeoGebra by mathematics educators (teachers and lecturers) in Indonesia. One of GeoGebra features is GeoGebra Applet that can be used, modified, and/or developed by educators for dynamic and interactive mathematics teaching and learning. At the time of research project, there is no GeoGebra Applets closely linked and aligned to the Indonesia national curriculum. The availability would be benefit for mathematics teaching and learning aligned to this curriculum. This research proceeds through seven steps of the Need, Capability, and Analysis (NCA) Model of Design and Development: 1) User Need Analysis; 2) Researcher as Developer Capability; 3) GeoGebra Applets Design; 4) GeoGebra Applets Development; 5) Experts Judgements; 6) Field testing in its Natural Setting Environment; and 7) the Prototype. The field testing was conducted with 8th grade students in a junior high school. The field testing shows that the developed Quadrilateral GeoGebra Applets can work as expected in its purposed natural setting environment.DOI: http://dx.doi.org/10.22342/jme.9.1.4162.27-40